Family as a Sovereign Institution - Góralski, Wojciech (Ecumeny and law, 2014)
Family, being the basic social unit and having its own identity, sovereignty, as well as its own fundamental rights, is a community conducive to life and the mission of the Church that, at the same time, constitutes the environment in which the Church actualizes herself. As John Paul II claims, "the Church thus finds in the family, born from the sacrament, the cradle and the setting in which she can enter the human generations, and where these in their turn can enter the Church. (Familiaris consortio, 15). The properly understood value of the family was heralded for example by Vatican II which emphasized that "the well-being of the individual person and of human and Christian society is intimately linked with the healthy condition of that community produced by marriage and family" (Gaudium et spes, 47). It also seems telling that a few significant post-Vatican II documents have been published by the papal Magisterium dealing with the topics of family and marriage. As another meaningful phenomenon there can be quoted the development of post-conciliar priesthood of families, as well as the establishment of manifold pro-family organizations. There can be no doubt as to the fact that family remains the contemporary Church’s centre of interest. In this age of various usurpations directed at identity and sovereignty of the family, the Chuch faces an extremely challenging task to decisively defend the revealed teaching on marriage and family.